MEANS OF IMPROVING THE FINANCIAL CONDITION AND STRENGTHENING THE FINANCIAL COMPONENT ECONOMIC SECURITY OF THE ENTERPRISE - HURYN, Vitalii; LOPATOVSKYI, Victor (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article emphasizes the relevance of planning and implementation of measures aimed at improving the financial condition in the context of strengthening the financial component of the economic security of the enterprise. The purpose of the study is to analyze and substantiate the means of improving the financial condition in the context of strengthening the financial component of the economic security of the enterprise.The roles (tasks) of improving the financial condition in the system of such components of the enterprise's economic security as financial, intellectual-personnel, technical-technological, marketing and institutional-legal are defined. A tree of tactical means of improving the financial condition in the projection of strengthening the financial component of the economic security of the enterprise has been developed. The strategic goals of the management system in the field of improving the financial condition in order to strengthen the financial component of the economic security of the enterprise are defined, namely - increasing the amount of income, reducing the level of expenses, increasing the level and amount of profit; strengthening of financial stability; strengthening of liquidity and solvency; increase in the market value of the enterprise; formation of an insurance and reserve fund; making investments to modernize the technical and technological base and strengthen the innovative component of competitiveness; improvement of the financial risk management system at the enterprise.The applied value of the research results consists in the development of a system of policy elements for improving the financial condition and strengthening the financial security of the enterprise in the form of a goal and a tree of tactical means of improving the financial condition in the projection of strengthening the financial component of the economic security of the enterprise.The scientific novelty of the research results lies in the further development of methodical and applied principles of managing the processes of ensuring the financial component of the economic security of the enterprise.
Keywords: enterprise; economic security; financial component; financial position; tools and means of strengthening